Centring Human Connections in the Education of Health Professionals - Melrose, Sherri (Athabasca University Press, 2020)
Many of today's learning environments are dominated by technology or procedure-driven approaches that leave learners feeling alone and disconnected. The authors of Centring Human Connections in the Education of Health Professionals argue that educational processes in the health disciplines should model, integrate, and celebrate human connections because it is these connections that will foster the development of competent and caring health professionals. Centring Human Connections in the Education of Health Professionals equips educators working in clinical, classroom, and online settings with a variety of teaching strategies that facilitate essential human connections. Included is an overview of the educational theory that grounds the authors' thinking, enabling the educators who employ the strategies included in the book to assess their fit within curriculum requirements and personal teaching philosophies and understand how and why they work.